The Academic Staff Stimulating Conditions and their Influence on the University's International Appeal - A. Y. Pleshakova; V. A. Tchupina (Russian State Vocational Pedagogical University, 2015)
The paper is aimed at finding the ways for stimulating the professorial teaching staff at foreign universities and the resulting effect of such stimulation on the university's international image and prestige. This issue is especially relevant in the context of Bologna Agreement and the Russian universities entering the global education area. The authors point out the following aspects of academic staff stimulation: material incentive, moral encouragement, improving the work environment, opportunities for professional growth, etc. In the course of the comparative analysis of foreign research materials, they single out the recruitment criteria and opportunities for career development as stimulating the academic stuff activity both in Russia and abroad; the conformities of the above processes being demonstrated. In the conclusion the authors maintain that the social well-being of the academic staff is closely related to the university's image. Therefore, it is recommended to balance the staff remuneration with the intangible reward package, career opportunities and flexibility in research and teaching activities.